Surface roughness optimization using Taguchi method of high speed end milling for hardened steel D2 - Al Hazza, Muataz Hazza Faizi; Ibrahim, Nur Asmawiyah; Adesta, Erry Yulian Triblas; Khan, Ahsan Ali; Abdullah Sidek, 'Atiah (IOP Publishing, 2017)
The main challenge for any manufacturer is to achieve higher quality of their final products with maintains minimum machining time. In this research final surface roughness analysed and optimized with maximum 0.3 mm flank wear length. The experiment was investigated the effect of cutting speed, feed rate and depth of cut on the final surface roughness using D2 as a work piece hardened to 52-56 HRC, and coated carbide as cutting tool with higher cutting speed 120-240 mm/min. The experiment has been conducted using L9 design of Taguchi collection. The results have been analysed using JMP software.